Analisis Proyeksi Kebutuhan Air Domestik dan Non Domestik pada Wilayah Kecamatan Penebel Kabupaten Tabanan - Suari, Putu Primantari Vikana; Astiti, Sagung Putri Chandra (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The number of springs and river flows is an indicator of the number of raw water sources available. As in Penebel Sub-district, where the available raw water sources can be utilised to meet the needs. The amount of water needed by the people of Penebel Sub-district depends on population growth. In general, the definition of clean water demand is the amount of water needed by the population in an area as a whole to fulfil their needs. The method implemented by researchers in analysing water demand is ‘domestic and non-domestic demand projection analysis’. There are several stages in this analysis, namely the stage of analysing the domestic water needed, the non-domestic water needed, the amount of water lost, the overall clean water demand, the average water demand, the maximum day factor and the peak hour day. The sample data analysed is the data of domestic and non-domestic clean water required from 2025 to 2031. Based on the analysis conducted, it was found that the domestic and non-domestic water demand in 2025 was 46.45 litres/second and 9.29 litres/second respectively and the average amount of water required was 66.89 litres/second. While in 2031 the domestic and non-domestic water demands were 54.01 litres/second and 10.80 litres/second respectively and the average amount of water required was 77.77 litres/second. So it is found that the projected population growth is directly proportional to the projected water demand.